If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(6x+8)=2(9x-12)
We move all terms to the left:
3(6x+8)-(2(9x-12))=0
We multiply parentheses
18x-(2(9x-12))+24=0
We calculate terms in parentheses: -(2(9x-12)), so:We get rid of parentheses
2(9x-12)
We multiply parentheses
18x-24
Back to the equation:
-(18x-24)
18x-18x+24+24=0
We add all the numbers together, and all the variables
48!=0
There is no solution for this equation
| 1/2x+5/18=31/63 | | 6(x+2)+3=29 | | 10+3u=25 | | 35n-108=312 | | 12+13x=11x | | 7-x/5=20 | | 31n-49=168 | | 33n-120=144 | | 40-x=4×-3-6x+6 | | 10(x-1)=90 | | 11/2+2/3x=37 | | 3(x-7)+4(x+4)=+ | | 156=4(8+7b)-3b | | 1/3x+4=1/8x | | 8x-4=28+4x | | x(2x+10)=546 | | 64+16m=288 | | 2x-5+3x-13=180 | | 64+m=288 | | 4(−x−2)−2x+5=31 | | 30n-48=192 | | 10=u/2-10 | | 0x+3=1x+9 | | x*(x+14)=108 | | 56(9x+9)=9576 | | 15=p*20 | | -8x^2+9x-4=0 | | 25n-14=336 | | 12.50+30x=15 | | -8+v=-2 | | 24n-12=276 | | x/9-28=19 |